2019
DOI: 10.1111/jmi.12822
|View full text |Cite
|
Sign up to set email alerts
|

Study of recovery and first recrystallisation kinetics in CGO Fe3%Si steels using misorientation‐derived parameters (EBSD)

Abstract: Summary Many metallurgical processes produce characteristic dislocation accumulation, with heterogeneous spatial and orientation distributions and further development of microstructures after heat treatment. Recovery and recrystallisation behaviours are direct consequences of those uneven dislocation distributions. The Electron BackScatter Diffraction (EBSD) technique can be used for the characterisation of such microstructural features, including: Density of Geometrically Necessary Dislocations (GND), Kernel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In a polycrystalline texture, the relative difference in crystallographic orientation between two neighbouring grains is called 'Misorientation', a local transformation in the crystallographic frame [46,47]. In coordinate systems, misorientation is described as the rotating of two grains with regards to their respective crystallographic directions.…”
Section: Ebsd General Texture Evaluationmentioning
confidence: 99%
“…In a polycrystalline texture, the relative difference in crystallographic orientation between two neighbouring grains is called 'Misorientation', a local transformation in the crystallographic frame [46,47]. In coordinate systems, misorientation is described as the rotating of two grains with regards to their respective crystallographic directions.…”
Section: Ebsd General Texture Evaluationmentioning
confidence: 99%
“…It is noted that the DRXed grains formed by CDRX or DDRX via grain boundary corrugation/bulging tend to have orientations similar to the parent grains [34,35]. The grain reference orientation deviation (GROD) map [29,36] for α-Mg grains is shown in Figure 12b. It is suggested that the Zr-rich coarse grain had substantial misorientations built up in the vicinity of boundaries, which supports the assumption that CDRX and DDRX were active in these regions [33].…”
Section: Analysis Of the Deformation/drx Mechanisms Of Zr-rich Coarse Grainsmentioning
confidence: 99%